Detection of the His-Heme Fe2+−NO Species in the reduction of NO to N2O by ba3-Oxidase from thermus thermophilus - Pinakoulaki, Eftychia; Ohta, Takehiro; Soulimane, Tewfik; Kitagawa, Teizo; Varotsis, Constantinos (My University, 2005)
Reaction pathways in the enzymatic formation and cleavage of the N-N and N-O bonds, respectively, are difficult to verify without the structure of the intermediates, but we now have such information on the heme a32+-NO species formed in the reaction of ba3-oxidase with NO from resonance Raman spectroscopy. We have identified the His-heme a 32+-NO/CuB1+ species by its characteristic Fe-NO and N-O stretching frequencies at 539 and 1620 cm -1, respectively. The Fe-NO and N-O frequencies in ba 3-oxidase are 21 and 7 cm-1 lower and higher, respectively, than those observed in Mb-NO. From these results and earlier Raman and FTIR measurements, we demonstrate that the protein environment of the proximal His384 that is part of the Q-proton pathway controls the strength of the Fe-His384 bond upon ligand (CO vs NO) binding. We also show by time-resolved FTIR spectroscopy that CuB1+ has a much lower affinity for NO than for CO. We suggest that the reduction of NO to NaO by ba 3-oxidase proceeds by the fast binding of the first NO molecule to heme a3 with high-affinity, and the second NO molecule binds to CuB with low-affinity, producing the temporal co-presence of two NO molecules in the heme-copper center. The low-affinity of CUB for NO binding also explains the NO reductase activity of the ba3-oxidase as opposed to other heme-copper oxidases. With the identification of the His-heme a 32+-NO/CuB1+ species, the structure of the binuclear heme a3-CuB1+ center in the initial step of the NO reduction mechanism is known
Keywords: Chemical bonds; Enzymes; Fourier transform infrared spectroscopy; Molecular structure; Protons; Raman spectroscopy; Ligands; Copper; Chemistry